Object Reconstruction From Fourier Magnitude Information Only - Tawfiq, A.J.; Hassan, F.N.; Mohammed, A. T. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Reconstruction an object from its Fourier magnitude has taken a great deal in the literature and there is still no obvious solution for the failure of this algorithm. In this paper, the frequent failure of the phase retrieval is discussed in details and it has been shown that when the object is cento-symmetric, the object support is vital element to ensure uniqueness while for asymmetric object; the asymmetric support of the object is not enough to ensure uniqueness but the reconstruction appear to include most of the information of the original object. This is also true for the reconstruction of a complex function.